1919 Wyo. Sess. Laws 17, ch. 17, § 1. - (:unkn) unknown (General Publisher, 1919)
It shall be unlawful for any person or company to store any gunpowder or any other explosive material at a less distance than one thousand feet from any house or habitation, when more than fifty pounds are at the same place; but it shall be unlawful to place or to keep any powder or other explosive material, in any house or building occupied as a residence, or in any outbuilding pertaining thereto.
--
Keywords: GUN POWDER STORAGE